The Close Relationship Between Teacher Charisma And Effective Teaching - Saroyan, Satenik (Զանգակ հրատ.)
The present paper is devoted to the study of teacher charisma. This trait is necessary for every teacher who seeks to achieve the desired result in the classroom. This article aims to define what traits are needed for a teacher to attract and motivate learners, determine how teacher charisma can affect student engagement, and show how it can change demotivated learners' attitudes. Moreover, the study focuses on the importance of certain teacher traits for imparting good knowledge, motivating learners, and molding strong and assertive individuals. Learners regain more confidence when a teacher supports and promotes them and is always ready to show, advise, and listen. Meanwhile, learners who are constantly criticized for mistakes in front of their peers or classmates often need more confidence. Considering these fundamental aspects of teaching, charismatic teachers always succeed in attracting interested, engaged, motivated, and self-confident students.
Keywords: Pedagogy; Psychology